5^(2x+1) = 2^(4x-3)
log 5^(2x+1) = log 2^(4x-3)
(2x+1)log5 =(4x-3)log2
(2x+1)/(4x-3) = log2/log5 = .43067
2x+1= .43067(4x-3) = 1.72268x - 1.29201
.27732x = -2.29201
x = - 8.26
2007-06-10 12:40:04
·
answer #1
·
answered by ironduke8159 7
·
0⤊
0⤋
5^(2x+1) = 2^(4x-3)
Take logs of both sides
So (2x+1)log5 = (4x-3) log2
so 2x log5 - 4x log2 = -3log2-log5
So x(2log5 - 4 log 2)= -3log2-log5
ie x = - { 3log2 + log5}/(2log5 - 4 log 2)
So by calculator x â - 2.703194
2007-06-10 19:01:11
·
answer #2
·
answered by Wal C 6
·
0⤊
0⤋
5^(2x+1)=2^(4x-3)
Apply log on both sides.
(2x+1) log5 = (4x-3) log2
2x log5 +log5 = 4x log2 -3log2
2x log5 -4x log2 = -3log2-log5
x ( 2 log5 - 4 log2 ) = -3log2 - log5
x = -3log2 - log5/ 2log5-4log2
For more assistance please visit www.classof1.com.
Classof1 - leading web tutoring and homework help.
Toll free - 1877-252-7763
2007-06-10 22:48:43
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Take natural log of both sides:
(2x+1)ln[5] = (4x-3)ln[2]
2x ln[5] + ln[5] = 4x ln[2] - 3 ln[2]
x(4ln[2] - 2ln[5]) = ln[5] - 3 ln[2]
x = {ln[5] - 3 ln[2]}/{4 ln[2] - 2 ln[5]}
2007-06-10 18:54:02
·
answer #4
·
answered by kellenraid 6
·
0⤊
0⤋
um there are two ways that i can think of but i am not sure which way you learned it
i highly doubt that those binomials are raised to a power of 5 and two but if they are, you will have to do FOIL mutliple times
otherwise if its the way i think which is distributive then you distribute the powers to the binomials and it would look like this
10x + 5 = 8x - 6
-8x -5 -8x - 5
2x=-11
x=-5.5
hope this helps
2007-06-10 18:49:00
·
answer #5
·
answered by Anonymous
·
0⤊
2⤋
i dunno... btw i hate pi :)
2007-06-10 18:46:01
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋